Comprehensive Analysis of Pediatric Pathology Cases (2022-2024): A Retrospective Study - Priyadharshini M, Priyadharshini M; Ramasubramanian, Abilasha; Ramani, Pratibha (Journal of Neonatal Surgery, 2025)
Background: Pediatric pathology cases encompass a wide spectrum of lesions, ranging from odontogenic cysts to benign tumors and fibro-osseous conditions. Understanding the prevalence, distribution, and treatment approaches is crucial for accurate diagnosis and effective management.Objective: This study aims to analyze pediatric pathology cases from 2022 to 2024, focusing on lesion types, patient demographics, laterality trends, and surgical interventions.Methods:A retrospective analysis was conducted on pediatric pathology cases reported between 2022 and 2024. Data on age, gender, diagnosis, laterality, affected regions, radiographic findings, and surgical interventions were collected and statistically analyzed.Results: A total of 87 pediatric cases were analyzed. Odontogenic cysts (32.2%) were the most frequently diagnosed lesions, followed by benign odontogenic tumors (12.6%), fibro-osseous and bone pathologies (10.3%), and soft tissue/salivary gland tumors (13.8%). A slight right-side predominance (50.6%) was noted, with the sexant five regions being most commonly affected (25.3%). Excision was the preferred treatment approach (79.3%). A subset analysis of the 2022( 40 cases) and the 2023 dataset (36 cases) revealed a higher female predominance in 2023 (60%) and a greater incidence of fibro-osseous and soft tissue/salivary gland tumors compared to 2022. Conclusion :Odontogenic cysts remain the most prevalent pediatric pathology, with benign tumors and fibro-osseous lesions also contributing significantly. Laterality trends varied across subsets, and excision was the dominant treatment approach. A multidisciplinary correlation of clinical, radiographic, and histopathological findings is essential for accurate diagnosis and management